Structural shifts in the Baltic States’ foreign trade - Vladimir G. Varnavskii (Baltic Region, 2024)
Professor Gennady Fedorov, Doctor of Geography and a distinguished Soviet and Russian researcher, made a significant contribution to the study of economic development in the Baltic states, particularly in their economic relations with Russia. His work consistently underscored the importance of trade with Russia for the Baltic economies and its impact on regional production of goods and services. Recent geopolitical shifts have triggered profound structural changes in international trade. This article examines the trade in goods within the Baltic states, as well as between these states and third countries, including Russia. It evaluates the long- and short-term structural shifts in commodity flows, utilizing a comparative analysis of export and import trends based on the latest international statistics. The study covers the period from 2004 to 2024, drawing on annual statistics from 2004—2023 and more granular quarterly and monthly data for 2021—2024, sourced from UN/UNCTAD, Eurostat, WTO, and the World Bank. Employing methods of statistical and structural analysis and Trade Intensity Index (TII) calculations, the article investigates two hypotheses. The first hypothesis, proposing a general increase in the TII between the Baltic states from 2004 to 2023, is partially supported; Lithuania’s exports deviate from the overall trend due to the country’s strong trade links with Poland and Germany. The second hypothesis, asserting the adaptability of Baltic business to geo-economic and geopolitical stresses — including sustained trade with Russia—has been fully confirmed. The article identifies commodity groups where export and import flows between the Baltic states and Russia increased between 2021 and 2023, highlighting potential niches for Russia to maintain or expand its presence.